Designing profile products as promotional media for brin publishers - Cempaka Destcarolina Natalita; Daniel Susilo (Jurnal Komunikasi Profesional, 2022)
The development of BRIN (Indonesian Research and Innovation Bureau) publishers today is inseparable from the important role of the development of Information and Communication Technology. Its utilization brings the community into the era of 4.0 whose use is through digital systems. Through these developments, BRIN Publishers are required to transform, the transformation carried out is a change in the offering that used to be physical products now into digital products and publishing services in the form of open access and utilizing social media as a tool in promotional media. Based on this, it encourages BRIN publishers to form promotional strategies using new media. Profile products are used as a promotional medium for BRIN publishers who are expected to create a good perception in building brand awareness and impact BRIN publisher engagement. This research uses a case study perspective, where one of the researchers takes an internship at the BRIN publisher The results of the profile product are expected to be an asset that can be officially uploaded into one of BRIN's social media platforms.